The Effectiveness of Pregnancy Exercise With Kinesio Taping on Lower Back Pain in Pregnant Women in the Third Trimester - Siti Mutoharoh; Dyah Puji Astuti; Kusumastuti Kusumastuti; Wulan Rahmadhani; Phan Trieu Phu MD (Faculty of Public Health, Sriwijaya University, 2021)
Lower back pain is common for pregnant women. The back pain was  caused by the shift of the center of gravity towards the front as the uterus enlarges. This study aims to determine the effectiveness of pregnancy exercise with the addition of Kinesio taping on low back pain in pregnant mother  at third trimester.The study used a quasi-experimental method and it was conducted in a rural area under the coverage area of a puskesmas in Kebumen District. The population in this study wasl pregnant women in the area with a total of 247 pregnant women. This study involved 36 pregnant women in the third trimester selected using a purposive sampling technique with the criteria of primiparous and multiparous, 28-36 weeks of gestation, experiencing low back pain, and no history of comorbidities and complications during pregnancy. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that pregnancy exercise with the addition of Kinesio taping had a significant effect on reducing low back pain in pregnant mother in the third trimester indicated by a P-value of 0.001.Pregnancy exercise with the addition of Kinesio taping can reduce low back pain in pregnant women in the third trimester.